Video Game Addiction: Consequences and Treatments - Viera-Riquelme, E (Institute of Electrical and Electronics Engineers Inc., 2021)
Addiction to video games is a disease recently recognized by the WHO that could increase due to the conditions of confinement caused by the pandemic resulting from COVID-19. This paper investigates the types of addictions, including the consequences of video game addiction in people. Research articles are analyzed, finding that the excessive use of video games is considered a behavioral addiction and is recognized by the DSM-5 as a mental disorder. The relationship between video games and the identified consequences is discussed, where it is proposed a set of consequences and treatments based on the literature review. However, there is still a lack of information about how to know if a gamer is addicted and how to treat the disease efficiently and safely. © 2021 IEEE.